2013
DOI: 10.1016/j.jpainsymman.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion for Control of Hot Flashes in Breast Cancer Survivors: A Prospective, Double-Blind, Randomized, Crossover, Pilot Phase II Trial

Abstract: Compared with placebo, bupropion did not control HFs in this group of BC survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…No increases in estradiol were noted while on testosterone cream, consistent with prior studies in women without history of breast cancer [ 35 40 ]. Two additional trials involving 115 participants intervened on hot flashes as the primary outcome with venlafaxine, clonidine or bupropion and examined if sexual function differed by these medications [ 41 , 42 ]. There were no differences in sexual function between women treated with venlafaxine compared to clonidine nor with women treated with bupropion versus placebo [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No increases in estradiol were noted while on testosterone cream, consistent with prior studies in women without history of breast cancer [ 35 40 ]. Two additional trials involving 115 participants intervened on hot flashes as the primary outcome with venlafaxine, clonidine or bupropion and examined if sexual function differed by these medications [ 41 , 42 ]. There were no differences in sexual function between women treated with venlafaxine compared to clonidine nor with women treated with bupropion versus placebo [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clonidine (C) then Venlafaxine (V) • One medication daily x 8 weeks • History of breast cancer 2. Venlafaxine, then Clonidine or vice versa • 2-week washout • ≥ 14 hot flashes/week • Second medication daily x 8 weeks • V: 75 mg once daily • C: 0.05 mg twice daily Nunez (2013) [ 41 ] To test bupropion on hot flashes • Sample size = 55 Two groups: 10-week intervention: 1. Sexual function (Arizona Sexual Experience Scale) • Median age 49, range 33-71 1.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, a few other antidepressants and antipsychotics have been reported to elicit a lower SD frequency in non-depressive patients than depressive patients, such as a 22.6% and 3% for patients being treated with fluoxetine and desipramine for lumbago ( Atkinson et al, 2007 ), and 29.8% with paroxetine for tinnitus ( Baldo, Doree, Molin, McFerran, & Cecco, 2012 ). Sexual function did not change under treatment with bupropion or venlafaxine ( Nuñez et al, 2013 ; Reed et al, 2014 ) and even improved with escitalopram compared with a placebo treatment for menopausal hot flashes in non-depressive women ( Reed et al, 2012 ). Therefore, the sexual adversity of antidepressants, like amitriptyline, is drug and disease codependent, and amitriptyline is safer for non-depressive patients than for those with depression.…”
Section: Discussionmentioning
confidence: 96%
“…Buproprion: In a randomized, double-blind, crossover, placebocontrolled pilot study of bupropion 150 mg in breast cancer survivors (N = 55), participants reported a larger reduction in hot flashes with placebo and a preference for placebo (Nuñez et al, 2013).…”
Section: Other Interventionsmentioning
confidence: 99%
“…A review of data from 375 participants in seven randomized, placebo-controlled clinical trials found that those receiving the placebo intervention reported an average decrease of 25% in hot flash frequency and scores at four weeks (Sloan et al, 2001). A small, double-blind, crossover study that compared bupropion to placebo reported a larger reduction in hot flashes in the placebo group and a preference for the placebo intervention (Nuñez et al, 2013). A small, double-blind, crossover study that compared bupropion to placebo reported a larger reduction in hot flashes in the placebo group and a preference for the placebo intervention (Nuñez et al, 2013).…”
Section: The Placebo Effect On Hot Flash Interventionsmentioning
confidence: 99%